Avaliação do temperamento emocional e afetivo em usuários de cocaína - Fuscaldo, Liane Velloso (2012)
BACKGROUND: Personality traits contribute to drug related behavior, but their role on cocaine experimentation, abuse and addiction is not yet clear. Our aim was to evaluate how emotional traits and affective temperament were associated with cocaine experimentation, abuse and dependence with a recently developed scale for the assessment of emotional (e.g. Anger, Volition) and affective temperaments (e.g. cyclothymic). An anonymous web-survey provides the optimal means to evaluate sensitive issues such as drug related behavior in the general population. METHODS: the data was collected in the Brazilian Internet Study on Temperament and Psychopathology (BRAINSTEP), which included the Affective and Emotional Composite Temperament Scale (AFECTS) and the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). The final sample consisted of 28,587 subjects (26.6% males, mean age=30.8 ± 9.8 yrs). Traits analysis controlled for age, gender, ethanol and marijuana use. RESULTS: For emotional traits, Inhibition (particularly caution), Coping and Control were significantly lower in the cocaine groups compared to controls, particularly in those with cocaine dependence. Anger and Desire increased in relation to the degree of cocaine involvement. The associations with Emotional Sensitivity and Volition were less robust. For affective temperaments, increased cocaine use was related to a lower proportion of stable types (obsessive, euthymic and hyperthymic) and the anxious type, and a higher proportion of cyclothymic and euphoric temperaments in both sexes. CONCLUSION: specific externalized and unstable traits were associated with cocaine related behavior. Addressing these traits may be important for recovery and prevention strategies.